Implementation of an Radar System using Arduino (International Journal of Food and Nutritional Sciences, 2022)
Radar was developed as a method of detecting enemy aircraft in World War 2. Along with thedevelopments in technology, these days it is used in a wide range of sectors. Since the last fewdecades, there have been significant advancements in the use of radar technology. In this project, wehave designed an Arduino radar using Ultrasonic Sensor for detection of Targets and measuringRange. An Arduino microcontroller makes electronics more discipline. This Arduino radar projectaims to achieve a radar system prototype based on an Arduino board that detects stationary andmoving objects. The radar system has different performance specifications, and it is also available ina variety of sizes. Distance measurements and Target detection can be visualized by Processingapplication. Processing application is visual arts-based software for learning to code.